Biocidal activity of the precipitated silica with surface compounds of Ag, Cu and Zn - Bogatyrov, V.M.; Galaburda, M.V.; Zaichenko, O.M.; Tsyganenko, K.S.; Savchuk, Ya.I. (Поверхность, 2015)
By modification of the highly dispersed silica surface with amino complexes of silver, copper and zinc from aqueous solution with further heat treatment, silica nanocomposites containing surface compounds of silver, copper and zinc were synthesized. The concentration of the silver in the samples was 1-2 wt%, and the copper and zinc - 1-5 wt%. Biocidal activity of the composites was tested against 18 different strains of micromycetes, phytopathogenic bacteria and algae. It was shown, that the highest efficiency is observed in the samples of silica modified with silver/copper and silver/zinc. Модифицированием поверхности высокодисперсного кремнезема амино-комплексами серебра, меди и цинка из водного раствора с последующей термообработкой, синтезированы кремнеземные нанокомпозиты, содержащие поверхностные соединения серебра, меди и цинка. Концентрация серебра в образцах составляла 1–2 %, а меди и цинка – 1–5 %. Биоцидная активность полученных композитов была изучена по отношению к 18 различным штаммам микромицетов, фитопатогенных бактерий и водорослей. Установлено, что наибольшая эффективность наблюдается в образцах кремнезема, модифицированного серебром/медью, а также серебром/цинком. Модифікуванням поверхні високодисперсного кремнезему аміно-комплексами срібла, міді та цинку з водного розчину з наступною термообробкою, синтезовано кремнеземні нанокомпозити, що містять поверхневі сполуки срібла, міді та цинку. Концентрація срібла в зразках становила 1–2 %, а міді та цинку – 1–5 %. Біоцидну активність одержаних композитів вивчали по відношенню до 18 різних штамів мікроміцетів, фітопатогенних бактерій і водоростей. Встановлено, що найбільша ефективність спостерігається в зразках кремнезему, модифікованого сріблом/міддю, а також сріблом/цинком.